2017
DOI: 10.1177/2332858417714457
|View full text |Cite
|
Sign up to set email alerts
|

Family Support of Third-Grade Reading Skills, Motivation, and Habits

Abstract: as recent education reform efforts in the United States have prioritized family engagement as central to school improvement plans, school districts must grapple with ways to develop home-school partnerships (Mapp & Kuttner, 2013). Under the Every Student Succeeds Act (ESSA) of 2015, school districts must reserve 1% of Title I funds to assist schools in carrying out activities that foster family engagement, which can include home-based reading programs that promote alignment between home and school activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
(83 reference statements)
1
15
1
7
Order By: Relevance
“…While building word recognition skills, reading comprehension was impacted. The scaffolding forms scores, for example, captured that there was a significant improvement in their ability to read after the process, which is aligned to what Capotosto et al, (2017) mentioned that learners have better performance when they have a vast range of vocabulary knowledge.…”
supporting
confidence: 70%
“…While building word recognition skills, reading comprehension was impacted. The scaffolding forms scores, for example, captured that there was a significant improvement in their ability to read after the process, which is aligned to what Capotosto et al, (2017) mentioned that learners have better performance when they have a vast range of vocabulary knowledge.…”
supporting
confidence: 70%
“…Previous studies have provided some evidence that parental involvement in reading activities and parents' beliefs about reading both have a causal effect on children's reading motivation and achievement and have correlation (Baker et al, 1997;Baker, 2003;Senechal and Young, 2008). For example, Capotosto et al (2017) state that in their study examining the effect of family support on the reading skills, motivation and habits of third-graders, students who receive family support make progress in these aspects. Pavalache-Ilie and Ţirdia (2015), on the other hand, reported that school performance was significantly related to parental involvement and intrinsic motivation in their study examining the relationship between parent involvement, school performance and intrinsic motivation of primary school third and fourth-graders.…”
Section: Increased Reading Motivation Through Parent-involved Reading...mentioning
confidence: 99%
“…The literacy component, especially reading, is very important as well since the latest information is gained and understood through reading activities. It will help the students to be able to keep up with information [4]. Furthermore, literacy in reading also makes the students have a lot of knowledge and know the latest information.…”
Section: Introductionmentioning
confidence: 99%